ANALISIS PERFORMA SISTEM PROPULSI PADA KAPAL SPOB AKIBAT PERGANTIAN GEARBOX - Wendhy Yozam; Abdul Gafur; Subagio Soim (Proceedings Conference on Marine Engineering and its Application, 2023)
In this final project, the performance of the propulsion system on the ship is analyzed SPOB.Sultan Samudera. With This is done to minimize errors in the selection or determination of gearboxesand other engines. The methods used are Engine Propeller Matching and Speed Power Predictionwhich will be compared with the sea trial report. Calculation of ship resistance is done manually usingthe Holtrop method at a speed of 10 knots, the results of engine propeller matching are used todetermine the Match Point obtained, based on the calculation of the resistance obtained by the ship'sresistance value Rt = 91.045 Kn. The power requirements obtained are 1658,000 HP on the 2 MainEngines used and 817,694 HP per engine based on the main engine that has been determined. Then thePropeller type is Ka 4-70 with P/Db 1.100 meters and propeller efficiency (?) 0.561, the propeller doesnot cavitate and the match point in rough hull conditions against Gearbox Ratio 7.42: 1 occurs at88.96% at 1900 rpm while at Gearbox Ratio 5: 1 rough hull conditions occurred at 290.74% at 1900rpm, then in the Speed Power Prediction conditions compared to the Sea Trial "Against the Current"at a speed of 8.8 knots, the match point was obtained at 1600 rpm at 8.1 knots, while at Gearbox Ratio5: 1 with a speed of 8.8 knots obtained a meeting point at 1160 rpm engine speed at 6.4 knots withknown Sea Trial results, so the Gearbox Ratio of 7.42: 1 is quite close to the actual data owned by thecompany with the calculations obtained.